Trend 2001 - 2006. Statistics Canada. CANSIM: Labor - Wages, Salaries and Other Earnings | Country: Canada | Province: Northwest Territories | Table: Family characteristics, husband-wife families, by wife's contribution to husband-wife employment income | Variable: Husband-wife families with 1 child, Average contribution of the wife to husband-wife family employment income | Units: # $CAD, 2001-2006. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-145. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Labor - Wages, Salaries and Other Earnings | Country: Canada | Province: Northwest Territories | Table: Family characteristics, husband-wife families, by wife's contribution to husband-wife employment income | Variable: Husband-wife families with 1 child, Average contribution of the wife to husband-wife family employment income | Units: # $CAD, 2001-2006. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-145. Dataset: Reports statistics on employment income in Canada, such as hourly wages, weekly earnings, and self-employment income, as well as compensation practices such as bonuses, commissions, and profit-sharing plans. Also included are data on earnings inequality, such as earnings differences between groups of workers (men versus women, university graduates versus high school graduates, or immigrant versus native-born workers), as well as data on minimum-wage earners. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Labor and Employment Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Salaries, Wages, Employment, Income